Cognitive flexibility in younger and older children who stutter - Paphiti, Maria; Eggers, Kurt (Frontiers in Psychology, 2022)
Purpose: Recent research findings suggest possible weaknesses in cognitive flexibility (CF) in children who stutter (CWS) when compared to children who do not stutter (CWNS). Studies so far, have been conducted with either younger (3–6 years old) or older children (6–12 years old) with a variety of measures. The purpose of the present study was to investigate CF with the use of a single behavioral measure across a broader age range (4–10 years old). Methods: Participants were 37 CWS (mean age = 6.90 years) and 37 age- and gender-matched CWNS (mean age = 6.88 years), divided in a younger (below 7 years) and older (above 7 years) age group. All participants undertook a computerized visual set-shifting task consisting of three blocks. CF was evaluated through across- and within-block comparisons of the actual response speed and accuracy values. In addition, mixing- and set-shifting-costs were evaluated based on the mean response speed and accuracy. Results: All participants showed expected mixing- and set-shifting-costs. Only the within-block analyses yielded significant between (sub)group differences. Investigation of the block × classification group × age group interactions showed that older CWS had larger set-shifting-costs (slowed down more and made more errors) compared to older CWNS. Conclusions: While all participants required more time during set-shifting trials, only the older CWS (7–10 years old), and not younger CWS, were slower and made more errors. This finding corroborates previous findings in CWS of a similar age and could possibly point to a role of CF in stuttering persistence.